Displays of belonging : Polish Jewish collecting and museums, 1891-1941 - Zarrow, Sarah Ellen (Cornell University Press, 2025)
"This book investigates the social and political role of local Jewish museums in Polish lands and in independent Poland from the 1890s up to the Holocaust, as well as Jewish ethnographic initiatives."